2016
DOI: 10.1002/jcla.22052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fetal RHD Genotype Including the RHD Pseudogene in Maternal Plasma

Abstract: Real-time PCR targeting RHD exons 5 and 7 simultaneously in maternal plasma is an accurate method for the diagnosis of fetal D genotype in our population. The RHD pseudogene real-time PCR assay is feasible and is particularly useful in populations with a high prevalence of this allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Some authors did not further explore when they suspected the presence of a maternal variant, provide inconclusive results to the clinicians and recommend RhIg prophylaxis 21–24 . Some other authors identified the mother's variant at varying degrees but provide the clinicians with inconclusive result notwithstanding the identified variant 6,17–19,25–28 . Finally, a minority of teams chose to report fetal RHD status to the obstetricians when this status could be deducted according to the exons not amplified in the maternal variant 29–33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors did not further explore when they suspected the presence of a maternal variant, provide inconclusive results to the clinicians and recommend RhIg prophylaxis 21–24 . Some other authors identified the mother's variant at varying degrees but provide the clinicians with inconclusive result notwithstanding the identified variant 6,17–19,25–28 . Finally, a minority of teams chose to report fetal RHD status to the obstetricians when this status could be deducted according to the exons not amplified in the maternal variant 29–33 .…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Some other authors identified the mother's variant at varying degrees but provide the clinicians with inconclusive result notwithstanding the identified variant. 6,[17][18][19][25][26][27][28] Finally, a minority of teams chose to report fetal RHD status to the obstetricians when this status could be deducted according to the exons not amplified in the maternal variant. [29][30][31][32][33] For instance, Parchure et al 32 resolved 6 out 13 inconclusive results and avoided unnecessary RhIg prophylaxis in two pregnant women while Hyland et al 33 resolved 5 out 12 inconclusive results and avoided RhIg prophylaxis in one case.…”
Section: 1%)mentioning
confidence: 99%
“…The classical method using end‐point PCR described by Singleton et al () is still widely used in the analysis of RHDψ . However, in recent years, other methods based on real‐time PCR have been proposed, including SYBR Green (Szulman et al, ) and Taqman assays (Ziza et al, ). According to the manufacturer (ThermoFisher, https://www.thermofisher.com/en/home/life-science/pcr/real-time-pcr/real-time-pcr-learning-center/real-time-pcr-basics/taqman-vs-sybr-chemistry-real-time-pcr.html), the Taqman method is superior to SYBR Green in several aspects, such as sensitivity, specificity, reproducibility and multiplexing potential.…”
Section: Discussionmentioning
confidence: 99%
“…The increased sensitivity of real‐time PCR has enabled its application in the detection of fetal RHDψ in maternal plasma to access the risk of haemolytic diseases of the fetus and newborn (Ziza et al, ). In addition, other advantages of real‐time PCR, such as its potential of automation, the rapid PCR performance and the reduced risk of contamination, make this method attractive for blood group genotyping (Polin et al, ).…”
Section: Discussionmentioning
confidence: 99%